Global existence and stability of a nonlinear wave equation with variable-exponent nonlinearities - Ghegal, Samah; Hamchi, Ilhem; Messaoudi, Salim A. (Applicable Analysis, 2020)
In this paper, we consider a nonlinear wave equation with damping and source terms of variable-exponent types. First, we use the stable-set method to prove a global result. Then, by applying an integral inequality due to Komornik, we obtain the stability result.